Harmonic effect between VSI and CSI using PWM control scheme - Muhammad Hifdzan Ilias (Universiti Malaysia Perlis, 2009)
The voltage source inverter (VSI) and current source inverter (CSI) are the type of inverters that commonly used today and mostly PWM (pulse width-modulation) drives. The functions of the inverters are for conversion from ac to dc source. These simulations are implemented in the PSIM program in order to study the harmonics effects. These simulations are implemented by using two types of loads which are RL load and the induction motor fed drive. The loads are connected in the three phase system due to the efficiency and effectively used compared to the single phase system. The main reason of these simulations is to study about the effects of the harmonics that produced by the drives and other passive components on the VSI and CSI circuits. These harmonics is occurred due to the electromagnetic interference (EMI) that produced by the components and the motor. The harmonics produced by these drives cause heat losses and reduce the efficiency of the machine and also cause vibrations in the rotor. Active and passive filters are some of the methods used to reduce the harmonics generated by these drives. This method is also used for THD improvement. The PWM control scheme is used to control the gate of the switches. This controller is commonly used and it is also easy to vary the switching frequency of the triangular-wave voltage source. Nevertheless, the VSI performances are more reliable and effectively used compared to CSI. The CSI are more expensive, less efficiency, difficult to vary, and high disturbances occurrences.